Techniques for Manufacture and Utilizing Liquid Organic Fertilizer (LOF) in Student Field Work Practices at the Gemilang Indah Tunas Utama Institute East Lombok - Suripto; Hidayati, Nurul; Ashiddiqi, Muktadi Amri (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This article is based on a practical fieldwork report from students of the Environmental Sciences Studies Program, Faculty of Mathematics and Natural Sciences, Mataram University at the Gemilang Indah Tunas Utama Institute, East Lombok. Student field work practice is a form of effort to increase the relevance between the theory obtained in lecture classes and practical work experience in the field. So in this way, students apart from gaining increased competence in certain academic fields also gain work experience which can improve managerial qualities, both hard skills and soft skills. The program that students participate in in this field work practice is the manufacture and use of liquid organic fertilizer (LOF). The method used for this activity includes lectures, discussions and practice accompanied by supervisors from the Research Division, Gemilang Indah Utama Institute, East Lombok and guided by lecturers from the Environmental Science Study Program, Mataram University. LOF Manufacture requires ingredients such as fruit peels and rotten fruit, banana stems, egg shells, lamtoro leaves and many more, the contents of which were previously known. The results show that the performance achievements of practical students are considered very satisfactory. Performance assessed includes practical employer satisfaction, discipline, enthusiasm, thoroughness, ability to choose priorities, ability to collaborate, ability to work independently, ability to absorb new things, and analytical ability. After participating in practical field work, students truly master the theory and are trained in selecting quality materials, making liquid organic fertilizer, preparing plant planting media in the form of direct land or plant media in plastic bags, making vegetable pesticides and applying liquid organic fertilizer.